MAKNA SIMBOLIK TEKS ESAI SEDANG TUHAN PUN CEMBURU KARYA EMHA AINUN NADJIB - ST Nurwahidah HS; Syamsudduha Syamsudduha; Faisal Faisal (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
The purpose of this study is to describe the shape of the symbols and to analyze the symbols contained in the essay text of the essay Medium God Is Jealous by Emha Ainun Nadjib. This research is a descriptive qualitative research. The method used in this study is an analytical method that produces data in the form of words, phrases and sentences. The research results obtained focus on the symbolic meaning of the essay text While God is Jealous by Emha Ainun Nadjib which is described through words or scientific language. Based on the analysis of the data and the discussion of the research, it was found that various forms of symbols were found, which, if examined in more depth, relied on harsh reality, honesty, truth, heartache, hope, rejection, and the author's suspicion of the reality that occurs in everyday life.